2015
DOI: 10.1177/1045389x15590275
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new torsional vibration damper incorporating conventional centrifugal pendulum absorber and magnetorheological damper

Abstract: Excessive torsional vibrations in mechanical systems with rotating mechanical components result in noise, excessive stresses, or even fatigue failure if not suppressed or controlled properly. Accordingly, they should be suppressed or controlled immediately to ensure system's reliability. In this study, a hybrid torsional vibration damper is proposed incorporating a conventional centrifugal pendulum vibration absorber and a magnetorheological damper. While centrifugal pendulum vibration absorbers are simple and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Consequently, these vibrations should be suppressed or controlled to a suitable value in order to ensure system's reliability. 1 The flexible unit that is installed at the designated position of the system transmission shaft, and the dynamic vibration absorber (DVA) which is placed on the designated unit of the system are currently the most commonly used control scheme for system torsional vibration suppression. Dual-mass flywheels (DMF), Centrifugal Pendulum Vibration absorber (CPVA), the DMF with CPVA, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these vibrations should be suppressed or controlled to a suitable value in order to ensure system's reliability. 1 The flexible unit that is installed at the designated position of the system transmission shaft, and the dynamic vibration absorber (DVA) which is placed on the designated unit of the system are currently the most commonly used control scheme for system torsional vibration suppression. Dual-mass flywheels (DMF), Centrifugal Pendulum Vibration absorber (CPVA), the DMF with CPVA, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrations can cause damage to the structure. Therefore, research harmful vibration is a matter of great concern to many scientists [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This vibration is particularly harmful, undesirable. Reduction of the shaft vibration is an important and timely task [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Abouobaia et al. 13 proposed a hybrid torsional vibration damper, which incorporated a conventional centrifugal pendulum vibration absorber and a magnet rheological damper. Howes et al.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Wu and Cheng 10 proposed a new design of the vibration absorber to reduce the torsional vibration of a crankshaft. Abouobaia et al 13 proposed a hybrid torsional vibration damper, which incorporated a conventional centrifugal pendulum vibration absorber and a magnet rheological damper. Howes et al 15 studied a compressor shaft broken because of torsional resonance, and found that the difference between theoretical analysis results and measured data was caused by the inaccuracy of shaft data.…”
Section: Introductionmentioning
confidence: 99%